GAYA DESAIN PADA INTERIOR RESTORAN DEWA NDARU CULTURE RESTO DI SURABAYA - Yuliani, Anggita Venesia; Wardani, Laksmi Kusuma (Dimensi Interior, 2012)
Dewa Ndaru Culture Resto is a restaurant designed with different interior styles to invite visitors to enjoy the cultural values and nostalgic experience of the past. Although the various styles have been implemented separately in terms of location, the design of the restaurant reflects a connection between the form and colour used in the interior space. The objective of this research is to analyse the combination of styles and how they have been applied in order to gain more knowledge regarding design styles, particularly in this restaurant. It is a qualitative mode of research which will be descriptive in its critical analysis to obtain verbal data and will depend on comparisons in which the findings would be in the form of a conclusion drawn to answer the summary of issues addressed previously. From the research findings, it has been found that Dewa Ndaru Restaurant has adopted cultural values from Traditional Java, Chinese houses, Colonial buildings and Modern restaurant designs.